Efecto de dos compuestos hormonales (pg600® y regumate®) en parámetros reproductivos y productivos en cerdas mestizas - Plúa Martínez, Miguel Ángel (2018)
This research was carried out at the ESPAM MFL Porcine Herd, in the El Limón site of Bolívar canton - Manabí, using 10 crossbred nulliparous sows (Landrace X Pietrain) of 8 months of age to evaluate the effect of gonadotropin hormones PG600® and Regumate® as heat synchronization protocols. The objective was to compare these two treatments in the reproductive and productive responses of the sows. In the distribution of the treatments, no experimental design was applied and the data were analyzed by means of the T test in the statistical program InfoStat / L that is used to compare only and exclusively the means between two groups and they were represented in simple bar graphs. The hormones were applied in the following manner PG600® 5 ml subcutaneously to each sow and REGUMATE® 5ml orally in the feed for 18 consecutive days. The results obtained show that there was no significant difference between the treatments for the variables of percentage of presentation of estrus, weight of piglets at birth and at weaning, percentage of piglet mortality and the benefit / cost index, while for time In response to heat induction and litter size there was a numerical difference, however, when subjected to the analysis in general statistics, no difference was found. It is concluded that the hormonal treatments favor the induction of estrus in nulliparous sows and quantitatively improve the size of the litter.